Expanding the measurement of police integrity. Issue 2 (16th May 2016) - Hickman, Matthew J.; Piquero, Alex R.; Powell, Zachary A.; Greene, Jack
Abstract : Purpose: – Klockars et al. use scenario methodology to measure perceived seriousness, level of discipline warranted, and willingness to report fellow officers engaged in various negative behaviors. These data are used to characterize the occupational culture of integrity in a given agency, relative to other agencies. What remains unclear is whether these agency-level findings mask important meso- and micro-level variation in the data (i.e. at the precinct/district and officer levels) that may contribute to a more complete understanding of an agency's culture of integrity. The paper aims to discuss these issues. Design/methodology/approach: – This study replicates and extends Klockars et al. 's work using data from a survey administered to 499 Philadelphia police officers, with the goal of both validating their methodological approach and exploring the need for multi-level theory in the study of police integrity. In addition to comparing the results from Philadelphia to those obtained by Klockars et al., the authors test for differences across officer demographics, and explore variance in the willingness to report various behaviors at both the officer- and district-levels. Findings: – Results indicate that bivariate relationships between officer-level demographics and willingness to report fellow officers are negated when controlling for theoretically relevant attitudinal variables such as cynicism and, consistent with Klockars et al., perceived seriousness of the underlying behavior. In addition, there is significant district-level variation in the average willingness to report fellow officers, and this variation can be explained by both organizational and environmental variables. On balance, the findings provide support for a multi-level approach to the study of police integrity. Originality/value: – While the Klockars et al. approach addresses macro-level variation in police integrity, this study contributes important findings at the meso- and micro-levels.